Landlord–Tenant Dilemma: How Does the Conflict Affect the Design of Building Energy Systems? - Larissa Kühn; Nico Fuchs; Lars Braun; Laura Maier; Dirk Müller (Energies, 2024)
To achieve climate goals, the European Union needs to increase building renovation rates. In owner-occupied buildings, energy cost savings provide financial incentives for renovation. However, 30% of all Europeans live in rented property, where conflicting stakeholder interests arise. Landlords are responsible for renovation decisions (building envelope and energy system) and the corresponding investments. Tenants face rising rents and only slightly benefit from falling energy costs. The literature calls this conflict the landlord–tenant dilemma. However, publications lack a quantification, leaving gaps in understanding its impact on technology choices and the heat transition. To address this, we incorporate the perspectives of landlords and tenants in a model-based approach for optimized technology choice (mixed-integer linear program). We compare optimal individual technology choices with the total cost optimum (including costs for landlords and tenants) for renovation decisions. Additionally, we examine how changes in the regulatory framework affect the economically driven landlord’s technology choice. Our study reveals that total costs and emissions are up to 60% and 283% higher for landlords deciding for rented houses compared to owner-occupied properties. Current approaches to solve the dilemma partly favor the development of climate-friendly energy systems. However, the renovation of the building envelope and operation costs are mostly disregarded in the decisions of landlords.